2018
DOI: 10.1075/avt.00010.vil
|View full text |Cite
|
Sign up to set email alerts
|

Voice and information structure in Surinamese Javanese

Abstract: This paper examines the grammatical voice system of Indonesian and Surinamese Javanese speakers. Alongside Javanese, the Surinamese speakers also speak Sranantongo and Dutch. Studying the use of voice in both speaker groups shows that it depends both on givenness and animacy of arguments. This interacts with the speaker group. The Surinamese speakers were found to be less discourse-dependent, due to general language contact processes as well as convergence to Dutch and Sranantongo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It could also be the case that heritage speakers perceive the di-prefix as a clear distinguishing feature of Javanese in contrast to the other language, and use it to emphasize this difference, as a sort of identity marker. This idea seems to be confirmed in a study by Villerius (2018b) on the use of voice in Surinamese Javanese. It was found that Surinamese heritage speakers use the undergoer voice with the same frequency as homeland Indonesian speakers, but that older heritage speakers use it more frequently than younger speakers, which could confirm this use as an 'identity marker' .…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It could also be the case that heritage speakers perceive the di-prefix as a clear distinguishing feature of Javanese in contrast to the other language, and use it to emphasize this difference, as a sort of identity marker. This idea seems to be confirmed in a study by Villerius (2018b) on the use of voice in Surinamese Javanese. It was found that Surinamese heritage speakers use the undergoer voice with the same frequency as homeland Indonesian speakers, but that older heritage speakers use it more frequently than younger speakers, which could confirm this use as an 'identity marker' .…”
Section: Discussionmentioning
confidence: 56%
“…Van Deusen-Scholl, 2003: 222). Because of this interrupted acquisition, proficiency in and usage of the heritage language varies greatly among speakers, and it offers a unique opportunity to investigate contact effects (see Villerius 2017Villerius , 2018aVillerius and 2018b for additional studies on contact effects in Surinamese Javanese). Suriname, as a former colony of The Netherlands, hosts a large variety of ethnic groups, brought together throughout the Dutch colonial rule.…”
Section: Background On the Speech Communitiesmentioning
confidence: 99%